Rariteiten op Reis De invloed van Albertus Seba’s contacten met reizigers op de totstandkoming van zijn rariteitenkabinet - Bos, Pauline (Studium, 2015)
Traveling curiosities. The influence of Albertus Seba’s contacts with travelers during the process of accumulation of his collection of curiositiesThe Amsterdam pharmacist Albertus Seba (1665–1736) gathered in his collection of curiosities a large and diverse range of specimens and objects, which aroused widespread admiration and interest. His collection consisted largely of exotic natural objects that were sent from overseas to contacts in the Dutch Republic. This method of gathering implied that a collector’s network of contacts with overseas travelers had a great impact on the composition of a cabinet. This article examines what Seba, in his descriptions, says about his network of contacts. This network indeed consisted mostly of people staying in exotic areas. The analyses brought to light that especially the quality, but also as the quantity of Seba’s contacts, were determining factors in the formation of his collection. Seba, in his Thesaurus, lists a large number of areas of origin of his specimens. However, there are significant differences in the number and type of objects coming from certain areas. Seba’s descriptions vary also considerably in length and content. They reflect the social nature of the production of knowledge in the early modern period, as these descriptions are based on a wide range of heterogeneous sources. This implies that collections of rarities may not be treated without reservation as an established and well-thought corpus of knowledge, but the contingent content and manner of formation of these cabinets need to be taken into account.